Effect Of Soil And Foliar Applications Of Zinc And Iron On The Yield And Quality Of Onion (Allium cepa L.) (Bangladesh Journal of Agricultural Research, 2013)
A field experiment was carried out at the research farm of National Research Centre for Onion and Garlic, Manjari, Pune (Maharashtra), India during kharif season of 2004 and 2005 to find out the effect of application of zinc and iron and their different modes of applications on growth, yield, and quality of onion. There were 27 treatment combinations with Zn and Fe were applied either in the soil or as foliar spray with cow dung slurry/FYM/gibbrelic acid/amino acids/2,4- D to onion. Application of Zn significantly increased the bulb weight (73.9 g), bulb yield (45 t/ha) when applied with 2,4-D (3 ppm) as foliar spray. Zinc application significantly influenced the bulb quality and recorded the highest A grade bulbs and the lowest poor quality C grade bulbs when applied with 2,4-D (81.9%) as foliar spray. The maximum medium B grade bulbs were obtained with the application of Fe with cow dung slurry (11.4%). Bangladesh J. Agril. Res. 38(1): 41-48, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15188